Silica-based waste form for immobilization of iodine from reprocessing plant off-gas streams - Matyáš, Josef; Canfield, Nathan; Sulaiman, Sannoh; Zumhoff, Mac (Journal of nuclear materials, 2016)
A high selectivity and sorption capacity for iodine and a feasible consolidation to a durable SiO2-based waste form makes silver-functionalized silica aerogel (Ag0-aerogel) an attractive choice for the removal and sequestration of iodine compounds from the off-gas of a nuclear fuel reprocessing plant. Hot uniaxial pressing of iodine-loaded Ag0-aerogel (20.2 mass% iodine) at 1200 °C for 30 min under 29 MPa pressure provided a partially sintered product with residual open porosity of 16.9% that retained ∼93% of sorbed iodine. Highly iodine-loaded Ag0-aerogel was successfully consolidated by hot isostatic pressing at 1200 °C with a 30-min hold and under 207 MPa. The fully densified waste form had a bulk density of 3.3 × 103 kg/m3 and contained ∼39 mass% iodine. The iodine was retained in the form of nano- and micro-particles of AgI that were uniformly distributed inside and along boundaries of fused silica grains. [Display omitted] •Silver-functionalized silica aerogel is an effective sorbent and a viable waste form for iodine.•Simultaneous application of fast heating rates and high pressures produced a fully dense product.•HIPing produced a fully consolidated waste form with a bulk density of 3.3 × 103 kg/m3 and containing ∼39 mass% of iodine.